Stoichiometric Release of SO2 from Adducts: Application to the Direct Synthesis of Protected Dienes - Martial, Ludovic; Bischoff, Laurent (Synlett, 2015)
The in situ, stoichiometric release of SO2 was studied from DABSO (DABCO adduct with SO2) and DMAP adduct. When involved in cheletropic additions, free SO2 released by this technique proved much more reactive than its adducts. Some examples of applications towards the direct synthesis of protected dienes from allylic alcohols are given.
Keywords: sulfur dioxide; dienes; sulfolenes